Social Media as Self-Reflection: Transforming Student Identity in the Digital Era - Sari, Nita Sofia; Nursanti, Meta; Gotama, I Kadek Dwiki; Kusuma, Candra; Yudhawati, Ine (Journal of Communication, Religious, and Social Sciences (JoCRSS), 2025)
This research examines the role of social media on the self-identity development of university students in the digital era. Using a descriptive qualitative method, this research investigates how social media platforms such as Instagram, TikTok, Twitter and Facebook shape students’ self-expression and identity construction. Data was gathered through in-depth interviews and a comprehensive literature review. The research reveals that social media provides a space for university students to experiment with self-identity outside of traditional social norms. However, it also poses challenges, such as social pressure and a potential gap between digital and real identities. Key findings suggest that social media can have both positive and negative impacts on students' identity formation. On the one hand, social media enables the development of self-confidence; on the other hand, it can cause social anxiety due to constant comparison with others. The research highlights the importance of wise use of social media in the context of identity formation, taking into account the psychological and social impacts that may arise.